Theurgy and Transhumanism (Revista Archai, 2020)
Theurgy was a system of magical practices in the late Roman Empire. It was applied Neoplatonism. The theurgists aimed to enable human bodies to assume divine attributes, that is, to become deities. I aim to show that much of the structure of theurgical Neoplatonism appears in transhumanism. Theurgists and transhumanists share a core Platonic-Pythagorean metaphysics. They share goals and methods. The theurgists practiced astrology, the reading of entrails, the consultation of oracles, channeling deities, magic, and the animation of statues. The transhumanist counterparts of those practices are genetics, self-tracking with biosensors, artificial intellects like Google and Siri, brain-computer interfaces, programming, and robotics. Transhumanist techno-theurgy shows how Neoplatonism can be a modern philosophical way of life.